The relationship between boll retention and defoliation of cotton at the fruiting site level. Issue 3 (9th April 2022) - Song, Xinghu; Zhang, Lijuan; Zhao, Wenchao; Xu, Daoqing; Eneji, A. Egrinya; Zhang, Xiang; Han, Huanyong; Cao, Longlong; Zhang, Wangfeng; Lu, Zhengying; Huang, Xiaoli; Wang, Hongzhe; et al.
Abstract: Defoliation is used to ease mechanical harvest and reduce lint staining of cotton ( Gossypium hirsutum L.). Crop conditions are important determinants of its efficiency, but their effects have not been fully examined. We performed a multiple‐site field study during 2018–2020 (under 17 environmental conditions, covering three cotton regions in China) to explore the relationship between boll retention and defoliation at the fruiting site level. The hormonal defoliant, thidiazuron and boll opener, ethephon, were tank‐mixed or their combination product was used in this study. There was a positive Spearman ranking correlation between boll retention and defoliation in most experimental sites, with correlation coefficients ( r ) ranging from .275 to .725 at 7 d after application of harvest aids, suggesting that the leaves at fruiting sites bearing bolls dropped more easily than those at fruiting sites where abscission occurred. The positive correlation declined with the fruiting sites up the plant and away the mainstem. The differences in defoliation between fruiting sites with or without bolls were high (around 60–70%) at lower and/or inner positions, but low or negligible at upper and/or outer positions. It appears that the higher light intensity at upper and outer portions of plant may enhance leaf drop and thus reduce the dependence of defoliation on boll retention. In conclusion, a high boll retention would accelerate leaf removal, and may enhance leaf abscission on cloudy days or within more closed canopy. Core Ideas: There was a significant positive correlation between cotton boll retention and defoliation. The positive correlation weakened over time. The positive correlation is closer at lower and first fruiting nodes than other position.